Pengalaman Publikasi Ilmiah Dosen CPNS Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Darmalaksana, Wahyudin (Gunung Djati Conference Series, 2025)
This study aims to discuss the scientific publication experience of lecturers of Civil Servant Candidates in 2025 at the Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung. This study uses a mixed method approach. The results and discussion show that 13 lecturers of Civil Servant Candidates have published 68 scientific articles with a distribution of 17 articles in national journals, 15 articles in Conference series, 2 articles in Sinta 1 indexed Scopus, 6 articles in Sinta 2, 9 articles in Sinta 3, 12 articles in Sinta 4, 2 articles in Sinta 5, 2 articles in international journals with global reputation indexed Scopus, and 3 articles in proceedings indexed Scopus. This experience illustrates that lecturers of Civil Servant Candidates are a potential resource for strengthening scientific publications in higher education, although their experience is uneven. This study concludes that lecturers of Civil Servant Candidates will be more productive in scientific publications through the formation of writing groups with a strategy of sharing experiences.